Exploring the Antimicrobial Potential of Moringa Oleifera Extracts Against Acinetobacter Baumannii: Antimicrobial Potential of Moringa Oleifera Extracts Against Acinetobacter Baumannii - Pervaiz, Saima; Zia, Afshan; Javed, Nida; Cheema, Sara Masood; Ahsan, Umaira; Haq, Ikram Ul; Shamim, Saba; Jahan, Shah (Pakistan Journal of Health Sciences, 2025)
Background setups around the world, especially in Asian countries. Published data explained the situation of extreme drug resistance and left patients with very few antibiotic options against this particular pathogen. Plant and their extracts are well known for their antimicrobial properties. Moringa oleifera is one of the prime plants with multiple applications in industries, especially in health care. Objective: To determine the antimicrobial activity of Moringa oleifera plant extracts against Acinetobacter baumannii. Methods: In this experimental study, ethanol extracts of Moringa oleifera root, stem, and leaves were prepared and tested against Acinetobacter baumannii by the well diffusion method and minimum inhibitory concentration method. Four concentrations of all three extracts were prepared as 5mg/ml, 10mg/ml, 15mg/ml, and 20mg/ml. All experiments were tested three times. Results: No inhibition was seen at 5mg/ml, a 6mm zone diameter was observed at 10mg/ml, and 11mm was seen at 15mg/ml. Conclusions: It was concluded that Moringa oleifera showed good inhibition activity against Acinetobacter baumannii. This study does not include the quality analysis of extracts; after quality analysis and precise concentrations could create a huge opportunity in dealing with this extremely drug-resistant pathogen.